1984
DOI: 10.1073/pnas.81.3.771
|View full text |Cite
|
Sign up to set email alerts
|

Interference of GTP hydrolysis in the mechanism of microtubule assembly: an experimental study.

Abstract: This paper reports an experimental study, of the interference of GTP hydrolysis in the mechanism of microtubule assembly, following the model and theory previously published [Hill, T. L. & Carlier, M.-F. (1983) Proc. Natl. Acad. Sci. USA 80,[7234][7235][7236][7237][7238]. Results from dilution experiments show that microtubules depolymerize faster below the critical concentration than expected with a reversible polymerization model. The experimental plot of flux versus tubulin concentration exhibits a slope di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
103
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(116 citation statements)
references
References 36 publications
(31 reference statements)
12
103
1
Order By: Relevance
“…This property, taken together with the placement of nucleating centers, can explain not only quantitative but also qualitative elements of microtubule organization. The notion that total tubulin levels are important to this mechanism is supported by in vitro experiments (5), by model building (20), and by demonstrations that cells appear to have mechanisms for regulating tubulin levels in response to changes in microtubule assembly (2,7). Other factors are likely to be involved as well.…”
mentioning
confidence: 74%
“…This property, taken together with the placement of nucleating centers, can explain not only quantitative but also qualitative elements of microtubule organization. The notion that total tubulin levels are important to this mechanism is supported by in vitro experiments (5), by model building (20), and by demonstrations that cells appear to have mechanisms for regulating tubulin levels in response to changes in microtubule assembly (2,7). Other factors are likely to be involved as well.…”
mentioning
confidence: 74%
“…10 suggest that packing alone is not sufficient to explain higher mobility of CAP-Gly assembled on microtubules because increased nano-to microsecond dynamics is found throughout the entire sequence rather than being limited to surface residues. We also note that the binding affinities of CAP-Gly to EB1 and microtubules are drastically different (high nanomolar versus mid-micromolar (12,19), and unpublished data), 3 and it will be instructive in the future to examine the possible connection between the thermodynamic binding parameters and the internal dynamics of CAP-Gly bound to EB1, assembled on MTs, and of CAP-Gly/EB1 complex associated on MTs. Such studies were reported in other systems (34 -36), where relationships 3 S. Ahmed and J. C. Williams, unpublished data.…”
Section: Discussionmentioning
confidence: 99%
“…heterodimers and are highly dynamic structures, undergoing continuous cycles of polymerization/depolymerization driven by the hydrolysis of GTP (2,3). Intracellular transport along the microtubules is accomplished by microtubule-associated motor proteins from dynein and kinesin families (4).…”
mentioning
confidence: 99%
“…Rescue is thought to occur when a rapidly shortening end becomes recapped with GTP-tubulin, a process which is infrequent in comparison to the rate of GDP-tubulin dissociation. Although the mechanism and location of GTP hydrolysis within a microtubule is controversial and unresolved (2,4,5,7,8,12,34,36,40,45), there is substantial support for the GTP cap hypothesis: (a) the bulk of polymer is GDP-tubulin (17,29,30,36,46,47); (b) elongation and rapid shortening are distinctly different phases (6,21,34,45); (c) GDP-tubulin subunits do not support elongation in buffers which permit dynamic instability (3); (d) rapid shortening occurs within seconds at both ends when GTP-tubulin association is prevented by dilution (Voter, W. A, and H. P. Erickson, manuscript in preparation; Walker, R. A., and E. D. Salmon, unpublished observations); (e) addition of a GTPase system to microtubules at steady-state results in polymer disassembly (3); (f) for both ends, dissociation during the rapid shortening phase typicaUy occurs at a constant rate as expected for a homogeneous core of GDP-tubulin subunits (21,45); (g) for both ends, there is a substantial dissociation rate during the elongation phase without any apparent phase transition (45); and (h) the critical concentration for elongation is similar at the two ends, suggesting that there is reversible dissociation (of GTPtubulin subunits) at both ends (45).…”
mentioning
confidence: 98%